ChemInform Abstract: Manganese(II) Salts as Efficient Catalysts for Chemoselective Transesterification of β‐Keto Esters under Non‐Conventional Conditions. Issue 23 (16th May 2013) - Krishnaiah, G.; Sandeep, B.; Kondhare, D.; Rajanna, K. C.; Reddy, J. Narendar; Rao, Y. Rajeshwar; Zhubaidha, P. K.
Abstract Since conventional conditions require reaction times of 16‐24h, the transformation of β‐keto ester (I) is investigated under ultrasound or microwave conditions where the latter afford optimal results concerning the time.